Design and Construction of a Variable Speed Drive Trainer as a Learning Medium for Electric Motor Installation at SMKS Sinar Husni 2 TR Labuhan Deli - Tampubolon, Ricky Nelson; Sembiring, Muhammad Aulia Rahman; Simanjuntak, Felix Hizkia (PTE FTK UIN Ar-Raniry, 2025)
A persistent mismatch between vocational education outcomes and industry requirements presents a global challenge, often stemming from limited student exposure to modern industrial technologies. This study addresses the gap by designing, developing, and validating a cost-effective Variable Speed Drive (VSD) trainer as a practical and pedagogically appropriate learning medium. The research employed the waterfall development model, encompassing a structured process of needs analysis, system design, hardware implementation, and comprehensive evaluation to ensure the trainer’s feasibility and instructional effectiveness. The evaluation phase included expert validation and practicality testing with end-users. Validation results showed the VSD trainer and accompanying job sheet were rated “Highly Suitable,” with average scores of 3.67 from media experts and 3.63 from subject matter experts on a four-point Likert scale. Practicality scores were 3.61 from teachers and 3.38 from students, indicating strong usability and instructional relevance in real classroom settings. The findings suggest that the VSD trainer is a validated, scalable, and effective instructional solution that improves students’ conceptual understanding, practical skills, and motivation. These outcomes align vocational training more closely with industry demands. Further development integrating IoT-based remote monitoring is recommended to enhance the trainer’s functionality and relevance in digitally supported learning environments.